2020
DOI: 10.3390/cancers12051187
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between ECOG-PS, mGPS, BMI/WL Grade and Body Composition and Physical Function in Patients with Advanced Cancer

Abstract: Cancer remains one of the leading causes of mortality worldwide and the associated reduction in physical function has a marked impact on both quality of life and survival. The aim of the present study was to examine the relationship between Eastern Cooperative Oncology Group-Performance status (ECOG-PS), modified Glasgow Prognostic Score (mGPS), Body Mass Index/Weight Loss grade (BMI/WL grade), and Computerised Tomography (CT)-derived body composition measurement and physical function in patients with advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
0
28
0
2
Order By: Relevance
“…Furthermore, in those patients, 42% had an elevated mGPS. One interpretation of the findings is that obvious weight loss in patients with advanced cancer is a later event than functional decline, and that functional decline is a later event than the development of a systemic inflammatory response [14]. Therefore, it may be that the mGPS should form the basis of stratification of likely survival in patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in those patients, 42% had an elevated mGPS. One interpretation of the findings is that obvious weight loss in patients with advanced cancer is a later event than functional decline, and that functional decline is a later event than the development of a systemic inflammatory response [14]. Therefore, it may be that the mGPS should form the basis of stratification of likely survival in patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent publication, the relationship between the mGPS and measures of physical activity was examined in patients with advanced lung cancer. 18 This study showed that an elevated mGPS was significantly and independently associated with poorer handgrip strength. Therefore, there is some evidence that the presence of the systemic inflammatory response is associated with a poor capacity for activity in patients with cancer.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study of patients with operable CRC, there was no direct measure of physical function made and so we were unable to explore the relationship between the systemic inflammatory response and physical activity in these patients. However, in a recent publication, the relationship between the mGPS and measures of physical activity was examined in patients with advanced lung cancer 18 . This study showed that an elevated mGPS was significantly and independently associated with poorer handgrip strength.…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index has been found associated with CRC postoperative complications and survival outcomes. However, traditional indexes, such as Mets, BMI, waist/hip ratio, and ECOG-PS, do not provide detailed quantitative data for clinical reference [ 15 ]. Recently, body composition has appeared as a substitution to the traditional index.…”
Section: Discussionmentioning
confidence: 99%